The Fundamental Aspects of the Cham Issue - Pacukaj, Sokol (Richtmann Publishing, 2012)
The Present paper would explain the most important aspects of the Cham issue. The populaiton mulsims chami wasdeported from Greece during the period 1912-1945 and the situation is still know unresolved. The cham conflict arose as a result of thedelineation of border between Greece and Albania at the end of Balkan Wars. During the period form June 1944 to March 1945 was thelast phase of expulsion of the Cham population from northern Greece, during which an estimated 5000 men, women and children werekilled. The rest of chami population fled over the border to Albania where they lived in exile ever since. The cham are demanding therecognition of all disappeared as a result of conflicts and the property right of all chami population. In this paper we will give some of thefoundamental aspects of the issue such are the recognition of the issue by the Greek government, the question of the lost citizenshipand the property rights.